Climate variability in SE Europe since 1450 AD based on a varved sediment record from Etoliko Lagoon (Western Greece). (1st March 2017) - Koutsodendris, Andreas; Brauer, Achim; Reed, Jane M.; Plessen, Birgit; Friedrich, Oliver; Hennrich, Barbara; Zacharias, Ierotheos; Pross, Jörg
Abstract: To achieve deeper understanding of climate variability during the last millennium in SE Europe, we report new sedimentological and paleoecological data from Etoliko Lagoon, Western Greece. The record represents the southernmost annually laminated (i.e., varved) archive from the Balkan Peninsula spanning the Little Ice Age, allowing insights into critical time intervals of climate instability such as during the Maunder and Dalton solar minima. After developing a continuous, ca. 500-year-long varve chronology, high-resolution μ –XRF counts, stable-isotope data measured on ostracod shells, palynological (including pollen and dinoflagellate cysts), and diatom data are used to decipher the season-specific climate and ecosystem evolution at Etoliko Lagoon since 1450 AD. Our results show that the Etoliko varve record became more sensitive to climate change from 1740 AD onwards. We attribute this shift to the enhancement of primary productivity within the lagoon, which is documented by an up to threefold increase in varve thickness. This marked change in the lagoon's ecosystem was caused by: (i) increased terrestrial input of nutrients, (ii) a closer connection to the sea and human eutrophication particularly from 1850 AD onwards, and (iii) increasing summer temperatures. Integration of our data with those of previously published paleolake sediment records, tree-ring-based precipitation reconstructions, simulations of atmospheric circulation and instrumental precipitation data suggests that wet conditions in winter prevailed during 1740–1790 AD, whereas dry winters marked the periods 1790–1830 AD (Dalton Minimum) and 1830–1930 AD, the latter being sporadically interrupted by wet winters. This variability in precipitation can be explained by shifts in the large-scale atmospheric circulation patterns over the European continent that affected the Balkan Peninsula (e.g., North Atlantic Oscillation). The transition between dry and wet phases at Etoliko points to longitudinal shifts of the precipitation pattern in the Balkan Peninsula during the Little Ice Age. Highlights: Southernmost varve record from the Balkan Peninsula spanning the Little Ice Age. Multiproxy sedimentological, paleoecological and geochemical analyses applied. Enhanced productivity post-1740 AD due to increased nutrient input and temperature. Varve microfacies is highly sensitive to climate change from 1740 AD onwards. Variability in precipitation assigned to North Atlantic Oscillation dynamics.